The views of patients with spinal cord injuries on their rehabilitation experience - D. J. Mothabeng; C. P. Malinga; C. van der Merwe; P. T. Qhomane; S. N. Motjotji (AOSIS, 2007)
Background and Purpose: Spinal rehabilitation programs seek to enhance the residual functional abilities of people who have an acquired disabling impairment because of SCI. Very little has been published on how patients experience rehabilitation, and what the implication of their experience is on rehabilitation outcomes. The aim of this pilot study was to explore the views of patients with SCI regarding their experience of rehabilitation while in hospital. Materials and Methods: A qualitative exploratory study using semi-structured interviews was employed. Twelve patients constituted the sample of convenience. Qualitative techniques were used to analyze the data. Results: The study revealed a variety of psycho-emotional issues related to the patients' experience of rehabilitation. Positive issues included being treated humanly, being told the truth about their condition early on, family involvement in rehabilitation and being allowed to contribute to decision making regarding their rehabilitation. Negative issues were mainly their lack of insight into their health condition. Conclusion: The study highlighted important psycho-emotional issues related to the patients' experience of rehabilitation. Rehabilitation personnel must consider these issues when working with patients with spinal cord injury, to ensure effective rehabilitation outcomes.